Konsep Tujuan Pendidikan Islam Menurut Imam Ghazali dan Guru Tua (Habib Idrus bin Salim Al-Jufri) - Saidi, Musdar; Hamami, Tasman; Wildan, Syakur (Institut Agama Islam Negeri (IAIN) Bone, 2023)
This research is a library research which reveals the thoughts of al-Ghazali and the Old Teacher about the purpose of education. The method used in this research is the documentary method. Some of the data collected includes primary and secondary data which discusses the educational thoughts of al-Ghazali and the Old Teacher regarding educational goals. Al-Ghazali is a great thinker and scholar with works in various fields of science including education. The greatest work of Imam Al-Ghazali is the book Ihya 'Ulum Ad-Din, where the purpose of education according to Al-Ghazali is a process of activities carried out systematically to give birth to progressive changes in human behavior, in order to form intellectual and noble morals in students. Such an old teacher is a great scholar and national figure, an educator in the land of Sulawesi, especially Central Sulawesi, the founder of the Al-khairaat educational foundation which now has a university. According to him, the aim of education, as the initial goal of Alkhairaat's founding, is to educate humanity, and that ideal education is not merely filling the brain but also educating all dimensions that exist in human beings, be it intellect, morals, spiritual and social. so that referring to these two objectives, both aim to develop the potential of students and form students who believe in God Almighty, and uphold morality and intellect.